Competition Is a Sin - Bolitho, Hector, 1897-1974 (Tufts Archival Research Center, 2006)
Hector Bolitho describes how he came to value solitude and leisure over the fear of being alone and the desire to be in constant competition with others. Audio also contains advertisement for "This I Believe" book.